Antidepressive Effectiveness of Amisulpride, Aripiprazole, and Olanzapine in Patients With Schizophrenia Spectrum Disorders: A Secondary Outcome Analysis of a Pragmatic, Randomized Trial (BeSt InTro). Issue 3 (May 2023) - Kjelby, Eirik; Gjestad, Rolf; Fathian, Farivar; Sinkeviciute, Igne; Alisauskiene, Renata; Anda, Liss; Løberg, Else-Marie; Reitan, Solveig Klæbo; Joa, Inge; Larsen, Tor Ketil; Rettenbacher, Maria; Berle, Jan Øystein; et al.
Abstract: Background: Depressive symptoms are frequent in schizophrenia and associated with a poorer outcome. Currently, the optimal treatment for depressive symptoms in schizophrenia remains undetermined. Amisulpride, aripiprazole, and olanzapine all have antidepressive pharmacodynamic properties, ranging from serotonergic affinities to limbic dopaminergic selectivity. Consequently, in a 12-month pragmatic, randomized clinical trial, we aimed to investigate differences in antidepressive effectiveness among amisulpride, aripiprazole, and olanzapine as a secondary outcome, measured by change in the Calgary Depression Scale for Schizophrenia sum score in patients within the schizophrenia spectrum. Methods: Psychotic patients within the schizophrenia spectrum were included, and effectiveness was analyzed with latent growth curve modeling. Results: Of the 144 patients, 51 (35%) were women, the mean age was 31.7 (SD 12.7), and 39% were antipsychotic naive. At inclusion, 68 (47%) participants had a Calgary Depression Scale for Schizophrenia sum score >6, indicating severe depressive symptoms. Across the 12-month follow-up, there was a depressive symptom reduction in all medication groups, but no statistically significant differences between the study drugs. Separate analyses of the subcohort with elevated depressive symptoms at inclusion also failed to find differences in depressive symptom reduction between study drugs. The reduction in depressive symptoms mainly occurred within 6 weeks after randomization. Conclusions: There was a reduction in depressive symptoms under treatment with amisulpride, aripiprazole, and olanzapine in acutely psychotic patients with schizophrenia spectrum disorder, but no differences between the drugs.